Analisis Tipologi Berdasarkan Indikator Fundamental Ekonomi Kabupaten Bangka Tengah - Zikri Rahmani; Tiara Fitari (Jurnal Manajemen Dirgantara, 2024)
Economic growth is one of the goals that all regions want to achieve. Economic growth is an indicator of the success of a region in planning strategies in that region. One of the drivers of economic growth is the influx of new investment into an area. To see a good investment, we need to first analyze the potential of the area. This research aims to identify investment opportunities in Central Bangka Regency based on the Klassen Typology for the 2018 - 2022 period as material for the government's evaluation in determining regional development priorities to achieve economic growth. The method used is a quantitative method with descriptive analysis. The data source used is data from the Central Bangka Regency Central Statistics Agency (BPS). Based on the research results, it is known that there are 2 industrial sectors in quadrant 1, namely the agriculture, forestry and fisheries sectors as well as the transportation and warehousing sectors. Quadrant II contains 8 sectors, namely the electricity and gas procurement sector, provision of accommodation and food and drink, information and communication, financial and insurance services, real estate, educational services, health services and social activities and other services. Quadrant 3 contains 5 sectors, namely mining and quarrying, industrial management, construction, wholesale trade and ECE and government administration. In sector IV there are 2 industries, namely water supply, waste management, waste and recycling, and other services.